ANALISIS PENGARUH LEADERSHIP STYLE DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MEMPERHATIKAN KOMITMEN ORGANISASI (Studi pada Pegawai Dinas Pendidikan dan Kebudayaan Kota Probolinggo) - Khusnul Khotimah; Nasharuddin Mas; Arief Purwanto (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this study was to obtain empirical evidence of the ability of leadership style and perceived organizational support in encouraging increased OCB, both directly and through the mediation of organizational commitment. This type of research is quantitative with the SEM-PLS method. Data were obtained through questionnaires distributed to 56 ASN employees at the Probolinggo City Education Office. The sample was determined by census or saturated sample.Empirical evidence shows that both leadership style and perceived organizational support are not directly able to encourage increased organizational citizenship behavior. However, if through the mediation of organizational commitment, then these two independent variables are able to strongly increase the organizational citizenship behavior of ASN employees at the Probolinggo City Education Office. This indicates that organizational commitment is able to act as a strong mediation (fully mediation).